2017
DOI: 10.1016/j.rpsmen.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Use of mobile technologies in patients with psychosis: A systematic review

Abstract: RESUMEN Introducción: Hay un creciente interés en las intervenciones mobileHealth (m-Health) en pacientes con psicosis. El objetivo de este estudio es realizar una revisión sistemática para analizar el estado actual de la investigación en este ámbito.Metodología: Búsqueda en las bases de datos PsycINFO, PubMED, SCOPUS, Medline, ISI Web of Knowledge e IME del CSIC. Intervenciones con tecnologías móviles en pacientes con psicosis.Resultados: De un total de 431 artículos se seleccionaron 20. Se diferencian tres t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 25 publications
1
12
0
3
Order By: Relevance
“…Smartphones, which are widespread and easily accessible, are a potentially viable mechanism to support the delivery of the care of first-episode psychosis [2]. People with psychosis commonly own Smartphones, use them in a similar way to the general population [3][4][5] and are willing and able to use digital health interventions (DHIs) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Smartphones, which are widespread and easily accessible, are a potentially viable mechanism to support the delivery of the care of first-episode psychosis [2]. People with psychosis commonly own Smartphones, use them in a similar way to the general population [3][4][5] and are willing and able to use digital health interventions (DHIs) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade there has been increasing research interest into the utilisation of online interventions for individuals with more serious mental illness, such as psychosis (Bonet et al, 2017; O'Hanlon et al, 2016). Preliminary research suggests that online interventions for psychosis are feasible and acceptable (Alvarez-Jimenez et al, 2014; Berry et al, 2016; Firth et al, 2016; Gay et al, 2016; Thomas et al, 2017), particularly for symptom monitoring and clinical management (Bell et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that people with psychosis are adopting digital technology in a similar way to the general population,18–20 and that they are interested in using mental health interventions delivered via Smartphones 21 22. A systematic review has found that interventions delivered through apps or text messaging on Smartphones are acceptable and feasible for people with psychosis and may support recovery 23. Smartphone apps based on self-management principles have shown promise in a wide range of long-term health conditions,24 and are a potential way to deliver accessible low-cost support to adults with psychosis.…”
Section: Introductionmentioning
confidence: 99%